PROFILE OF DECREASED CONSCIOUSNESS IN GERIATRIC PATIENTS AT H. ADAM MALIK HOSPITAL MEDAN IN 2018 - Harun Andreas, Arianto Purba, Bistok Sihombing, Dina Aprilia & Dewi Fuji Lestari (International Journal of Research Science and Management, 2020)
Introduction: The decline in consciousness, disruption of either the level or content of consciousness, is a significant problem in the ER (Emergency Room). The incidence varies from 4% to 10%. It is an emergency medical condition that requires proper evaluation and initial management in the ER. Fluid and electrolyte imbalance disorders leading to loss of consciousness among hospitalized geriatric patients and the infection and effects of the drug. Delirium is closely related to dehydration, a multifactorial problem associated with some physiological changes in old age. Aim: This research aims to know about the decline profile of consciousness in geriatric patients in RSUP H. Adam Malik Medan in the year 2018. Methods: This descriptive-analytic study used retrospective design by collecting the medical record data of the patients who had been consul to the geriatric division in 2018. There are 1391 research subjects taken in total sampling. Data analysis is presented in the form of the frequency distribution of respondents characteristics including age, gender, primary diagnosis of loss of consciousness, electrolyte examination, and head of CT-scans and analysis by using the Kruskall-Wallis test to determine the relationship age with the incidence of loss of consciousness due to electrolyte imbalance. Data analysis using SPSS 20th. Result: Obtained by the most five diseases that cause a loss of consciousness in geriatric patients, i.e., electrolyte imbalance (imbalance) 876 people (63.0%), ischemic stroke 155 people (11.1%), sepsis as many as 141 (10.1%), hemorrhagic stroke 89 people (6.4%), and hypoglycemia 69 (5.0%). Geriatric patients with electrolytes imbalance due to hyponatremia (89.3%) and hypokalemia(28.53%). There is no association between the age and the electrolyte levels of geriatric patients, p>0.05. Conclusion: Decreased consciousness in geriatric patients is most due to electrolyte imbalance.